Silo-best and Sila-ferm additives for corn silage and drought-stressed corn silage for yearling steers - Bolsen, K.; Ilg, H. (Kansas State University. Agricultural Experiment Station, 2011)
Normal corn silage, with and without additives, and drought-stressed corn silage were evaluated in a 77-day growing trial using 64 steers. Steers fed drought silage had slowest and least efficient gains. Additive-treated silages were used more efficiently than the control silage. Dry matter recovery from the silos was consistently improved by the enzyme additive but not by the microbial inoculant additive. Steer gain per ton of corn crop ensiled was increased by 7.2 and 4.4 lb for enzyme and inoculant silages, respectively, compared with that for the control silage.
Keywords: Beef; Corn silage; Additive; Enzyme